Which Part of a Short, Global Risk Assessment, the Risk Instrument for Screening in the Community, Predicts Adverse Healthcare Outcomes?. (5th August 2015) - O'Caoimh, Rónán; FitzGerald, Carol; Cronin, Una; Svendrovski, Anton; Gao, Yang; Healy, Elizabeth; O'Connell, Elizabeth; O'Keeffe, Gabrielle; O'Herlihy, Eileen; Weathers, Elizabeth; Cornally, Nicola; Leahy-Warren, Patricia; et al.
Abstract : The Risk Instrument for Screening in the Community (RISC) is a short, global risk assessment to identify community-dwelling older adults' one-year risk of institutionalisation, hospitalisation, and death. We investigated the contribution that the three components of the RISC ( concern, its severity, and the ability of the caregiver network to manage concern) make to the accuracy of the instrument, across its three domains (mental state, activities of daily living (ADL), and medical state), by comparing their accuracy to other assessment instruments in the prospective Community Assessment of Risk and Treatment Strategies study. RISC scores were available for 782 patients. Across all three domains each subtest more accurately predicted institutionalisation compared to hospitalisation or death. The caregiver network's ability to manage ADL more accurately predicted institutionalisation (AUC 0.68) compared to hospitalisation (AUC 0.57, P = 0.01 ) or death (AUC 0.59, P = 0.046 ), comparing favourably with the Barthel Index (AUC 0.67). The severity of ADL (AUC 0.63), medical state (AUC 0.62), Clinical Frailty Scale (AUC 0.67), and Charlson Comorbidity Index (AUC 0.66) scores had similar accuracy in predicting mortality. Risk of hospitalisation was difficult to predict. Thus, each component, and particularly the caregiver network, had reasonable accuracy in predicting institutionalisation. No subtest or assessment instrument accurately predicted risk of hospitalisation.